Lumbosacral Fusion Using Instrumented Cage Distraction–Fixation in a Dog with Degenerative Lumbosacral Stenosis - Reints Bok, Tjarda E.; van Stee, Lucinda; Willemsen, Koen; Beukers, Martijn; Grinwis, Guy C.M.; Meij, Björn P. (VCOT Open, 2020)
This study aimed to assess the long-term outcome and intervertebral fusion following surgical distraction and stabilization using an intervertebral cage and pedicle screw and rod fixation (PSRF) in a dog with severe degenerative lumbosacral stenosis (DLSS).Degenerative lumbosacral stenosis is a common disorder in large breed dogs and has a multifactorial origin. Surgical treatment by dorsal laminectomy and discectomy results in decompression of neural structures, but when distraction–fixation is applied, the ultimate goal is vertebral fusion. A 4-year-old male neutered Leonberger, presented with DLSS and pre-existent chronic discospondylitis, was treated by dorsal laminectomy, partial discectomy, curettage of the end plates, distraction with an intervertebral spacer (SynCage), and PSRF. At 26 months after surgery, the Helsinki pain score and neurological Griffith score were improved; however, the dog passed away shortly thereafter due to an unrelated disorder. The lumbosacral segment became available for computed tomography (CT), micro-CT and histopathology. On CT, bone volume through the largest hole of the cage was 91.0% and for compact bone 76.1%. Micro-CT and histopathology revealed vertebral fusion. Distraction–fixation using an intervertebral spacer and PSRF was well-accepted in this dog with severe DLSS, and the dog had a good clinical outcome with long-term follow-up. CT, micro-CT and histopathology showed evidence of vertebral fusion.
Keywords: distraction-fixation; degenerative lumbosacral stenosis; cage; intervertebral cage